Outcomes and complications of exposed Kirschner wire f ixation for metacarpal fractures: a retrospective study - Andrea Cruciani; Silvia Pietramala; Alessio Greco; Alessandro El Motassime; Camillo Fulchignoni; Lorenzo Rocchi (Medicinski glasnik, 2026)
Aim: Metacarpal fractures are common hand injuries, frequently treated with closed reduction and internal fixation (CRIF) using Kirschner wires (K-wires). While exposed K-wires allow for simple hardware removal and early mobilization, their use is traditionally associated with a higher risk of pin tract infections. There is a lack of studies focusing exclusively on exposed K-wires in metacarpal fractures. Methods: It was retrospectively reviewed 134 patients who underwent CRIF with exposed K-wires for metacarpal fractures between January 2023 and March 2024. After applying inclusion and exclusion criteria, 118 patients were analyzed. Demographics, fracture characteristics, complications, and follow-up data were collected. Functional outcomes were assessed using the QuickDASH and the Michigan Hand Outcomes Questionnaire (MHQ) before hardware removal. Results: Most patients were male, 88 (75%), with a mean age of 39.3 years. The little finger was the most frequently injured, 71 (60%). In 102 (86%) cases, a single metacarpal fracture was observed. The average number of wires used was 1.7, and hardware was removed after a mean of 40.1 days. The rate of pin tract infection was <4%, all classified as superficial and managed conservatively. Only one case required reoperation due to secondary displacement. The mean QuickDASH score was 25, and the average MHQ score was 70.15, indicating overall good functional and patient-reported outcomes. Conclusion: Exposed K-wire fixation for metacarpal fractures appears safe and reliable, with low complication rates and favorable patient-reported outcomes, supporting its use in outpatient pathways without compromising safety.
Keywords: device-related infections; hand bones; retrospective studies; treatment outcome